Features tendency cosmic in contemporary Iraqi configuration (Al-Academy, 2017)
The research current ( features tendency cosmic in contemporary Iraqi configuration) attempt to study the dimensions of the conceptual and philosophical foundations upon which the tendency of cosmic within the period that extended its influence beyond the place where I grew up to be circulated concepts in all parts of the world, it is no doubt that the world is now heading to rapprochement after the tremendous developments in the field of communication technology and reflected heavily on identity concepts, privacy, the concept of nation-states ... etc. to become an individual and a large area of access to other cultures, and all that aroused the interest of contemporary Iraqi artist this interest arising from the desire to keep up with developments in the world of developments at the level of ideas or at the level of their practical applications in the field of art. So promising researchers studied four chapters, the first chapter of it concerned with the methodological framework for the search represented research problem which is determined by answering the following two questions: - What are the features of the universal tendency that emerged in the products of contemporary art!? - Is it possible to identify those features and levels of formal and technical Alamadaminah artists Fine Iraqis across Mndzhm Fine!? The first chapter also included a goal Find a (detection features tendency cosmic in contemporary Iraqi art) The boundaries of research has been limited to the study of the features of the tendency of cosmic and analysis of pictorial models for artwork Iraqi contemporary in the time period (1990-2010) performed by artists Iraqis inside and outside Iraq The materials are different, then Chapter mentioned terminology entitled Find seal, either disconnect the second has included a presentation of the theoretical framework, which included three sections, the first of it (the concept of cosmic and privacy) and taking second section (features tendency cosmic in contemporary global Fine Arts), and display the third section (Find approaches between the contemporary global art and contemporary Iraqi Art) and ended Chapter indicators theoretical framework. Chapter III has specialized display research procedures in terms of monitoring the research community and information related to the selection of a sample of it deliberate manner, which amounted to (35) in accordance with Cecchelaa and by (4) models of the sample covered the limits Find the adoption of the descriptive approach and the way the descriptive analysis for the purpose of analysis. Chapter IV brought together the results of research and conclusions as well as recommendations and proposals, followed by the list of sources